2012
DOI: 10.5539/ijef.v5n1p112
|View full text |Cite
|
Sign up to set email alerts
|

Using Environmental and Social Information in Lending Decisions

Abstract: There is no doubt that collecting and analysing information is the key element in the process of decision making. Lending decisions, taken by banks, are not exception. In order to ensure that lending decisions are serving banks' goals, the process of taking such decisions involves, inter alia, gathering and analysing information about the prospective and actual clients, who are seeking loans. Such information is mainly related to the financial performance of banks' clients. The recent trend of considering info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This agrees with the Ismail (2016), Elsaldt & Worthington (2013), Mio & Marco (2013), Al-shekhali (2012), and Thompson & Cowton (2004) studies which indicated that, credit officers need extra information to assess the risks that may affect the companies' ability to repayment and that disclosing the financial, strategic, economic, environmental and social information enhances the decisions of credit officers when taking the credit decision, and that there is a significant role to the variables of credit granting decision in taking the banking credit decision at Jordanian commercial banks.…”
supporting
confidence: 92%
“…This agrees with the Ismail (2016), Elsaldt & Worthington (2013), Mio & Marco (2013), Al-shekhali (2012), and Thompson & Cowton (2004) studies which indicated that, credit officers need extra information to assess the risks that may affect the companies' ability to repayment and that disclosing the financial, strategic, economic, environmental and social information enhances the decisions of credit officers when taking the credit decision, and that there is a significant role to the variables of credit granting decision in taking the banking credit decision at Jordanian commercial banks.…”
supporting
confidence: 92%
“…Elsakit and Worthington [30] explored the extent to which banks and lending institutions consider information other than financial when analyzing customer information for loan application. Particularly in developing countries, banks and lending institutions enforce the use of environmental and social information when evaluating a loan request rather than promote this requirement by the power of the law.…”
Section: Factors Affecting Risk Managementmentioning
confidence: 99%
“…Particularly in developing countries, banks and lending institutions enforce the use of environmental and social information when evaluating a loan request rather than promote this requirement by the power of the law. In developing countries, the process of making lending decisions without taking the impact of external environment is risky, because the external environment includes legal environment, awareness of society, the ability of the client to produce such information, and perception of environmental and social responsibility [30].…”
Section: Factors Affecting Risk Managementmentioning
confidence: 99%
“…He was actually highlighting the deficiency in legislation, which does not hold banks accountable for financing polluting projects. Elsakit and Worthington [2013] mentioned the risks associated with the environmental issue, namely; indirect risk, direct risk and reputational risk. The first two result from the existence and implementation of environmental legislation.…”
Section: Legislation and Risks Associated With Environmental And Soci...mentioning
confidence: 99%